2013
DOI: 10.1002/anie.201304887
|View full text |Cite
|
Sign up to set email alerts
|

{Mo24Fe12} Macrocycles: Anion Templation with Large Polyoxometalate Guests

Abstract: POM and circumstance: Nanometer-sized polyoxometalates (POMs) bring a new direction to anion-templated supramolecular chemistry. The Keggin (left) and Dawson-type (right) polyoxoanions direct the assembly of giant metallomacrocycles through an array of weak hydrogen-bonding interactions. The concerted action of multiple hydrogen bonds keeps the templating guests embedded within the hosts, even in the solution state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…A stabilizing anionic template effect, resulting from the presence of a tightly encapsulated BF 4 – anion in 1 , may offer an explanation for this trend. 20 …”
Section: Resultsmentioning
confidence: 99%
“…A stabilizing anionic template effect, resulting from the presence of a tightly encapsulated BF 4 – anion in 1 , may offer an explanation for this trend. 20 …”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Their intrinsically anionic nature, variable charge,s ize,a nd redox activity make them ideal candidates for the functional aniondriven assembly of architectures. [7,8] Forinstance,ithas been shown that the intrinsic formation of {Mo 36 }u pon acidification of molybdate allows the self-assembly of the {Mo 154 }giant Mo-blue macrocycle, [9] opening the way for the formation of the family of gigantic polyoxomoblybdates ranging in nuclearities from 36 to 368. In this respect it is increasingly thought that the host-guest [{Mo 36 }&{Mo 150 }] system is the gateway to these architectures, [10] being the key intermediate that directs the self-assembly of an otherwise,i mpossible or highly improbably set of structures.…”
mentioning
confidence: 99%
“…Since the first report of organic light-emitting diodes fabricated from tris(8-hydroxyquinolinolate) alumimum (III) (Alq 3 ) in 1987 [12], group 13 complexes have attracted much attention due to their variety of structures, adequate electron transport, and luminescent properties [13][14][15][16][17]. Inspired by the prominent work of M. C. Hong, J. Zhang, O. M. Yaghi and their co-workers [18][19][20][21], we considered that indium is a good candidate for construction of CPs due to its larger ion radii, and more fascinating coordination properties than that of B, Al, and Ga. However, the most challenging from the synthesis process, the recognized bottleneck, is hydrolysis of group 13 metal (III) salt [22] .…”
mentioning
confidence: 99%